Assessment of the impact of anemia on the treatment of acute bronchiolitis cases (Annals of Medical Research, 2024)
Aim: Acute bronchiolitis is a clinical condition characterized by inflammation of the bronchioles, primarily caused by viral agents in children under two years of age. The cornerstone of treatment includes hydration and oxygenation, while patients should be closely monitored for potential complications. Our objective is to evaluate the impact of anemia on treatment outcomes in children diagnosed with acute bronchiolitis.Materials and Methods: Children aged 1-24 months diagnosed with mild or moderate acute bronchiolitis in a tertiary pediatric health and disease clinic were retrospectively included in the study. Demographic characteristics and bronchiolitis severity (mild/moderate) were recorded. Pre- and post-treatment clinical severity, respiratory rate, heart rate, oxygen saturation levels, and bronchiolitis clinical scores were analyzed. The clinical findings and treatment responses of anemic and non-anemic patients were compared. A p-value of
Keywords: Bronchiolitis; Anemia; Hypoxia; Respiratory distress